Guttate Psoriasis Can Present With Psoriatic Arthritis after Urinary Tract Infection: Case Report - Suad Hannawi; Issa Al Salmi (Dermatology, 2016)
Introduction: Psoriasis and psoriatic arthritis (PsA) are serious, poorly understood, diseases. As many as 10-30% of psoriasis patients develop an inflammatory arthritis termed psoriatic arthritis which is progressive and leads to destruction of the joints if it is not treated assertively. Several triggering factors may elicit or aggravate the expression of psoriasis, of which focal infections is a well-established triggering factor, in particular infections of the upper respiratory tract. Guttate (eruptive) psoriasis, known to have a better prognosis than other types of psoriasis with rapid involution and longer remission, but its clinical course has barely been studied. We are presenting a case of guttate psoriasis with sever onset and association with nail psoriasis, scalp psoriasis and psoriatic arthritis, all which started unexpectedly after urinary tract infection Case Presentation: We are presenting a young woman of 32-years-old who presented to our service with a typical guttate psoriasis lesion after urinary tract infection. Her guttate psoriasis exhibited unusual sever course with associated onset of nails psoriasis, scalp psoriasis, conjunctivitis and psoriatic arthritis. All the symptoms started few days after urinary infection symptoms. Conclusion: Guttate psoriasis that occurs after urinary tract infection, may exhibit sever onset and rapid progression to psoriatic arthritis.